2000
DOI: 10.1016/s0893-133x(00)00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Cocaine Decreases Cardiac Vagal Tone, Vagal Index (Derived in Lorenz Space), and Heart Period Complexity (Approximate Entropy) in Cocaine Abusers

Abstract: We assessed the effects of i.v. cocaine on parasympathetic and sympathetic nervous system activity, and on the complexity vs. regularity of changes in heart rate over time. Fourteen otherwise healthy men with histories of i.v. cocaine abuse received bolus injections of cocaine (20 mg or 40 mg) and placebo (saline) on different days.Cardiovascular measures derived from the electrocardiogram, including heart rate, Porges' vagal tone (respiratory sinus arrhythmia), the 0.10 Hz rhythm, Toichi's vagal index, Toichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
2
12
1
1
Order By: Relevance
“…The ApEn reflects the repetition of complex patterns (for review: 7) in the fluctuation of the beat-to-beat periods. Clinical investigations have reported that ApEn decreases during cocaine-evoked arrhythmia (16), general anesthesia (17), in infants that have had episodes of aborted suddeninfant-death syndrome (18), in patients with high risk of sudden cardiac death (10), and in heart transplant patients (19). Our result established that the immediate postictal stage, characterized by a transient loss of entropy in beat-to-beat periods, might consist of a short episode with putative risk of lethal cardiac complication in epilepsy patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ApEn reflects the repetition of complex patterns (for review: 7) in the fluctuation of the beat-to-beat periods. Clinical investigations have reported that ApEn decreases during cocaine-evoked arrhythmia (16), general anesthesia (17), in infants that have had episodes of aborted suddeninfant-death syndrome (18), in patients with high risk of sudden cardiac death (10), and in heart transplant patients (19). Our result established that the immediate postictal stage, characterized by a transient loss of entropy in beat-to-beat periods, might consist of a short episode with putative risk of lethal cardiac complication in epilepsy patients.…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated for m ‫ס‬ 3, and ApEn was the difference between the values at m ‫ס‬ 2 and m ‫ס‬ 3. To normalize r to a fixed percentage of the time-series SD, which is the standard implementation of ApEn, gives ApEn a translation and scale invariance (18), so it remains unchanged under uniform process magnification, reduction, or constant shift, and it is decorrelated from SD analysis (14)(15)(16)(17).…”
Section: Heart-rate Variability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This and other 'chaos' derived parameters have proven valuable in the area of cardiovascular pathology, for example in discriminating cardiac patient groups with respect to the dynamics of their cardiovascular system. RSA and ApEn have been found to be significantly correlated (Newlin et al, 2000), but are by no means identical. For example, their mathematical foundation is quite different.…”
mentioning
confidence: 94%
“…Можно предполагать, что при более длительной регистрации сердечного ритма (до трех часов) будет наблюдаться постепен-ное возрастание его сложности, но более медленное, чем первоначальное снижение, так как фаза элиминации в кинетике этанола значительно более длительная, чем фаза резорбции. Интересным является тот факт, что подобное наблюдаемому в наших данных снижение сложности сердечного ритма показано и для острого введения кокаина (вероятно, еще од-ного «дедифференциатора»), причем ApEn снижается в этом случае тем больше, чем выше вводимая доза (Newlin et al, 2000). Таким образом, снижение сложности сердечного ритма не только качественно отражает наличие системной дедифференциации, но и, по всей ви-димости, количественно связано с ее степенью.…”
Section: обсуждение результатовunclassified